KAJIAN ARKEOLOGI KEWILAYAHAN PAPUA: HASIL-HASIL, STRATEGI DAN PROSPEK - Mahmud, M. Irfan; Suroto, Hari (BALAI ARKEOLOGI PAPUA, 2012)
Based on the results achieved demonstrate the scope of the research and development of archaeological studies covering seven themes, namely: (i) human and cultural end of the Pleistocene, (ii) human and Austronesian culture, (iii) the early history of civilization, (iv) the influence of Islamic civilization (v) the influence of colonial civilization, (vi) assessment of public archeology, and (vii) maritime archeology. Jayapura Archeology do four step strategy of dividing the focal areas of research, establish policy follows national archaeological assessment, which consists of nine themes, conduct integrated research, mapping the research level typology of three types: (i) basic research / pure research (ii) research applied (iii) ad hoc research. In addition to research in rural areas also need to be conducted in the coastal areas tertama outer islands of Papua.